The Line of Thought in Romans 7,15-20 - Lambrecht, Jan (Biblica, 2004)
The parallelism between Romans 7,14-17 and 18-20 as it has recently been put forward by O. Hofius is critically examined. It would seem that within this text Paul’s reasoning progresses from vv. 14b-16 to 17-20. The thesis of v. 14b ("I am fleshly, sold into the slavery under sin") gives way to the more sophisticated pronouncement of v. 17 ("as a matter of fact it is not I that do the evil, but the indwelling sin"). Each time motivations follow, vv. 15 and 18-19; finally a conclusion is drawn, vv. 16 and 20.